2021
DOI: 10.1038/s41598-021-87152-8
|View full text |Cite
|
Sign up to set email alerts
|

The 2011 Tohoku-oki tsunami-induced sediment remobilization on the Sendai shelf, Japan, from a comparison of pre- and post-tsunami surface sediments

Abstract: Tsunamis are generally considered to disturb the seafloor, rework surface sediments, and change seafloor environments. However, the response of the seafloor to such extreme wave events has not been fully elucidated. Herein, we compare the surface sediments before and after the 2011 Tohoku-oki tsunami on the Sendai shelf and demonstrate that both sandy and muddy sediments were significantly reworked on the shelf. Muddy sediments (> 10 cm thick) were redeposited as graded mud with no or little bioturbation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Due to the very long periods of tsunami waves, water movement occurs throughout the whole water column, reaching the seabed even at great depths [ 80 , 91 , 99 ]; it is therefore capable of setting sediments at depths well below storm wave base in motion [ 99 102 ]. Moreover, sea level drop between successive tsunami waves can lead to the emergence of vast areas subsequently prone to erosion [ 93 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the very long periods of tsunami waves, water movement occurs throughout the whole water column, reaching the seabed even at great depths [ 80 , 91 , 99 ]; it is therefore capable of setting sediments at depths well below storm wave base in motion [ 99 102 ]. Moreover, sea level drop between successive tsunami waves can lead to the emergence of vast areas subsequently prone to erosion [ 93 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tsunamis can disturb the seabed and rework offshore sediments. Investigations after the 2011 Tohoku tsunami in Japan showed redeposited mud and sorted sand layers on the Sendai shelf down to ~ 100 m water depth (Ikehara et al, 2021). Also, resuspended sediments were carried offshore and continued down the slope to deep water, as turbidity currents (Arai et al, 2013).…”
Section: Full Textmentioning
confidence: 99%
“…Second, transportation of sediments by the tsunami-backwash from the shelf to the slope could develop into turbidity currents causing erosion and redeposition as the suspension cloud of sediments runs down slope to the deep ocean. Deposits from both these processes were documented from sea oor surveys after the Tohoku tsunami in 2011, on the Sendai shelf and in the deep ocean outside the Sendai shelf (Arai et al, 2013;Ikehara et al, 2021) For long wave tsunamis, such as the one generated by the Storegga Slide, the currents are uniform from the surface to near the water/sediment interface at the sea oor and are a function of surface elevation (wave amplitude) and water depth. The maximum horizontal ow velocity, u max, in a propagating tsunami can then be approximated to the maximum surface elevation η max through the expression:…”
Section: Offshore Currents Generated By the Storegga Tsunamimentioning
confidence: 99%
“…Large earthquakes and tsunamis have enough potential to disturb sea floor, remobilize surface sediments and form submarine earthquake-and tsunamiinduced event deposits (e.g., Ikehara and Usami, 2018). Recent studies have suggested that tsunami-induced sediment resuspension and tsunami backwash can transport shallow marine sediments to the deep sea (Feldens et al, 2009;Ikehara et al, 2021a). Tsunami-induced turbidity currents by the 2011 Tohoku-oki earthquake were observed by instrumental records at two sites off Sanriku upper slope (Arai et al, 2013) and tsunami-induced turbidites were recognized on the outer shelf-upper slope (Ikehara et al, 2014(Ikehara et al, , 2021bUsami et al, 2017) along the Japan Trench.…”
Section: Introductionmentioning
confidence: 99%